“What are Left from Learning during the Pandemic?” EFL Students’ Problems and Strategies in E-Learning Platform - Apriliani, Reni Pradifta; Puspitasari, Dewi (Journal of English Teaching and Learning Issues, 2022)
This study aimed to review the implementation of online learning and EFL students' problems and strategies in learning English using the E-learning platform during the Covid-19 pandemic. This research design implemented a qualitative approach by using narrative inquiry. The data collection technique was done by semi-structured interviews, while the data analysis used Braun and Clark’s thematic analysis. The result showed that learning English using E-learning at Senior High School covered downloading learning material, forums, and exercises. In the implementation of online learning, several problems were faced by students, including the difficulty in managing time, equipment, and technical needs such as weak signal, limited quota, inadequate gadgets, teacher’s lack of explanation in learning material, and listening skills, which were not effective. Meanwhile, students utilized these strategies to overcome challenges. It included organizing time management, utilizing free internet data packages, utilizing diverse abilities in the learning environment, asking subject teachers via private chat via WhatsApp, requesting assistance from classmates (peer tutoring), performing autonomous learning, and searching for additional references or sources and supporting videos. Thus, this study depicts the challenges encountered by EFL students that teacher can use in encouraging their students to solve problems using these strategies.